A Detailed Paleoclimate Proxy Record for the Middle Danube Basin Over the Last 430 kyr: A Rock Magnetic and Colorimetric Study of the Zemun Loess-Paleosol Sequence - Laag, Christian; Hambach, Ulrich; Zeeden, Christian; Lagroix, France; Guyodo, Yohan; Veres, Daniel; Jovanović, Mladjen; Marković, Slobodan B. (Frontiers in Earth Science, 2021)
In mid-latitude Eurasia, loess-paleosol sequences provide the most widespread sedimentary records of Quaternary paleoenvironmental evolution. In the Middle Danube Basin, these archives cover at least the last million years of climate history, and occasionally contain archaeological finds. The studied Zemun profile is located on the right bank of the Danube in Northern Serbia. It was declared as a protected site, based on Palaeolithic artefacts found on the riverbank stemming from unknown stratigraphic levels of the loess cliffs exposed along the Danube. In order to provide a stratigraphy and to place the Zemun site into an environmental and temporal context, it was investigated by means of environmental magnetic and colorimetric methods. Our investigations result in a chronostratigraphic scheme allowing for direct comparison with well-established reference records in the Middle Danube Basin. Two tephra layers are recognized, which we assign to the L2 tephra and the Bag tephra. Our integrated age model suggests the quasi-continuous accumulation of mineral dust from marine oxygen isotope stage 11 to 5 (c. 430 to 50 ka). Our integrative approach reflects a continuous aridisation over the last four interglacial/glacial cycles and we discuss potential changes in seasonality.